Interpretation of genotype × year interaction in rainfed durum wheat under moderate cold conditions of Iran. Issue 1 (2nd January 2017) - Mohammadi, Reza
ABSTRACT: A multi-year trial was conducted to compare the effects of genotype, year and genotype × year (G×Y) interactions for grain yield and several drought-adaptive traits of 25 wheat genotypes during five seasons (2005–2010). Four conventional stability statistics, covering a wide range of stability concepts (Types 1–4), and the additive main effect and multiplicative interaction (AMMI) model were applied to analyse G×Y interaction and to investigate the causes of G×Y interaction in rainfed durum wheat. For all the traits, the largest sum of squares (SS) was accounted for by the year, followed by G×Y interaction and genotype effects. Most of the G×Y interaction (73.4%–90.6% of total G×Y interaction) was of crossover type, which would complicate the development of genotypes with stable performance. Partitioning SS due to G×Y interaction for genotypes indicated that the breeding lines were the smallest contributors to crossover G×Y interactions. The results indicated that the freezing days and earliness were among the climatic and genotypic co-variables, respectively, that contributed most to the G×Y interaction in rainfed durum wheat.